Parenting Styles Shaping Academic Achievement and Student Discipline: Gaya Pengasuhan yang Mempengaruhi Prestasi Akademik dan Disiplin Siswa - Iskandar, Iskandar; Ridwan, Muh; B, Muhammad Rusmin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the digital era, moral degradation among young learners poses a critical challenge, necessitating effective character education strategies rooted in national and religious values. Specific Background: The Proyek Penguatan Profil Pelajar Pancasila (P5) and Profil Pelajar Rahmatan Lil Alamin (PPRA) have been implemented separately in Indonesian schools to foster holistic student development. However, in madrasah contexts, the integration of both frameworks remains limited. Knowledge Gap: Previous studies examined P5 or PPRA individually, with scarce evidence on their combined impact in shaping students’ character, especially in areas with strong local cultural values such as Bulukumba. Aims: This study investigates the influence of the integrated P5 and PPRA (P5P2RA) projects on the character formation of Grade IV students in KKMI Region I, Bulukumba Regency. Results: Using a quantitative correlational design with 165 respondents, data analysis revealed a positive and significant effect (β=0.454, p<0.05), with the model explaining 57.7% of character development variance. Novelty: This is among the first empirical studies integrating P5 and PPRA into a unified, contextually adapted framework for Islamic primary education. Implications: Findings highlight the strategic role of integrated character education projects in strengthening students’ moral, social, and civic values, suggesting their scalability to other madrasah settings to foster a generation that is religiously grounded, socially responsible, and globally competent. Highlights: Integration of P5 and PPRA in one framework. Significant positive effect on character formation. Applicable model for Islamic primary schools. Keywords: Character Education, Pancasila Student Profile, Rahmatan Lil Alamin, Madrasah Ibtidaiyah, Educational Integration